Challenges and evolution of the Italian National Health Service: between crisis and reform - Pierpaolo Di Micco; Egidio Imbalzano; Carmine Siniscalchi (Italian Journal of Medicine)
Dear Editor, The Italian National Health Service (Servizio Sanitario Nazionale), established in 1978, was designed to provide equitable access to comprehensive care for all citizens. Founded on universality, equity, and solidarity, and funded mainly through taxation, it has achieved major public health successes, such as hepatitis B vaccination campaigns and cancer screening initiatives...